'All the time watched': an analysis of disciplinary power within the Irish Direct Provision system. Issue 3 (17th February 2022) - Hewson, Dominic
ABSTRACT: Initially launched as a temporary measure, Direct Provision is two decades old and home to 7, 400 asylum seekers. Since inception, it has been the target of internal and external criticisms along with academic scrutiny documenting the system's functions and failings. This article builds on these analyses to examine the crucial role fulfilled by disciplinary power in maintaining the system and conducting its residents. It draws upon Michel Foucault's ideas regarding the application of power in carceral institutions to examine common experiences of observation, normalisation, hierarchisation and examination as related by Direct Provision residents. Their testimonies detail aspects and effects of a complex system reliant on discipline to conduct conduct at the 'street level', while also working alongside other modalities of power to influence broader strategies of population management and governance.